Effect of Influenza Vaccination Inducing Antibody Mediated Rejection in Solid Organ Transplant Recipients - Cordero, Elisa; Bulnes-Ramos, Angel; Aguilar-Guisado, Manuela; González Escribano, Francisca; Olivas, Israel; Torre-Cisneros, Julián; Gavaldá, Joan; Aydillo, Teresa; Moreno, Asunción; Montejo, Miguel; Fariñas, María Carmen; Carratalá, Jordi; et al. (Frontiers in Immunology, 2020)
Introduction Our goal was to study whether influenza vaccination induced antibody mediated rejection in a large cohort of solid organ transplant recipients (SOTR). Methods Serum anti-Human Leukocyte Antigen (HLA) antibodies were determined using class I and class II antibody-coated latex beads (FlowPRATM Screening Test) by flow cytometry. Anti-HLA antibody specificity was determined using the single-antigen bead flow cytometry (SAFC) assay and assignation of donor specific antibodies (DSA) was performed by virtual-crossmatch. Results We studied a cohort of 490 SOTR that received an influenza vaccination from 2009 to 2013: 110 (22.4%) received the pandemic adjuvanted vaccine, 59 (12%) within the first 6 months post-transplantation, 185 (37.7%) more than 6 months after transplantation and 136 (27.7%) received two vaccination doses. Overall, no differences of anti-HLA antibodies were found after immunization in patients that received the adjuvanted vaccine, within the first 6 months post-transplantation, or based on the type of organ transplanted. However, the second immunization dose increased the percentage of patients positive for anti-HLA class I significantly compared with patients with one dose (14.6% vs. 3.8%; P = 0.003). Patients with pre-existing antibodies before vaccination (15.7% for anti-HLA class I and 15.9% for class II) did not increase reactivity after immunization. A group of 75 (14.4%) patients developed de novo anti-HLA antibodies, however, only 5 (1.02%) of them were DSA, and none experienced allograft rejection. Only two (0.4%) patients were diagnosed with graft rejection with favorable outcomes and neither of them developed DSA. Conclusion Our results suggest that influenza vaccination is not associated with graft rejection in this cohort of SOTR.